Determinants of breastfeeding duration in Shiraz, Southwest Iran - Zarshenas, M.; Zhao, Yun; Scott, Jane; Binns, Colin (MDPI, 2020)
A prospective cohort study was conducted in Shiraz in the south west of Iran to investigate breastfeeding from birth to six months of age. Mothers were recruited in a face-to-face interview within 48 h of giving birth in three public and two private hospitals (n = 700). They were then followed-up at 4, 12, 16, and 26 weeks postpartum in local Maternal and Child Health Clinics. Upon being discharge from hospital, 98.7% of mothers were breastfeeding and 74.3% were ‘fully’ breastfeeding, but only 29.9% of mothers had breastfed ‘exclusively’ since birth. The median duration of ‘full’ breastfeeding was 13 weeks and less than 1 week for exclusive breastfeeding. In a multivariable Cox proportional hazard regression, after adjustment, shorter durations of ‘exclusive’, ‘full’, and ‘any’ breastfeeding were associated with the introduction of a pacifier. The in-hospital use of formula and prelacteal feeds were also associated with a shorter duration of full and any breastfeeding. Breastfeeding on demand at 3 months and beyond was associated with a longer duration of breastfeeding. The risk factors associated with the premature discontinuation of breastfeeding identified in this study are all related to the “Ten steps to successful breastfeeding” and the Baby Friendly Hospital Initiative (BFHI). The principles that the BFHI provide are reaffirmed in this study as the basis for future breastfeeding promotion programs.